Comparison of children's self-reports of depressive symptoms among different family interaction types in northern Taiwan - Yen Lee-Lan; Kao Chi-Hsien; Wu Wen-chi; Lee Tony (BMC, 2007)
Abstract Background Previous research has shown that family interactions are associated with depressive symptoms in children. However, detailed classifications of family interaction types have not been studied thoroughly. This study aims to understand the types of family interactions children experience and to identify the specific types of family interactions that are associated with a higher risk of depressive symptoms in children. Methods Data used in the study was collected as part of the Child and Adolescent Behavior in Long term Evolution (CABLE) project in 2003. CABLE is a longitudinal cohort study that commenced in 2001 and collects data annually from children in Taipei city and Hsinchu county in northern Taiwan. The data analyzed in this study was that obtained from the sixth graders (aged 11 to 12 years old) in 2003. Of the 2,449 sixth graders, 51.2% were boys and 48.8% were girls. Factor analysis and cluster analysis were used to investigate the types of family interactions. One way ANOVA was used to establish the relationship between family interaction types and children's self-reports of depressive symptoms. Results Based on the results of factor analysis, the latent factors for family interactions included supporting activities, psychological control, parental discipline, behavioral supervision, and family conflict. After conducting cluster analysis using factor scores, four types of family interactions were revealed: supervised (29.66%), disciplined (13.56%), nurtured (40.96%) and conflict (15.82%). Children from the disciplined or conflict families were more likely to report depressive symptoms. Children from the nurtured families were least likely to report depressive symptoms. Conclusion Family interactions can be classified into four different types, which are related to children's self-reports of depressive symptoms. The creation of a family interaction environment that is beneficial for children's mental health is an important issue for health education and health promotion professionals.